Biosynthesis and Lipase-Catalysed Hydrolysis of 4-Hydroxybutyrate-Containing Polyhydroxyalkanoates from Delftia acidovorans - Diana Hooi-Ean Ch’ng; Wing-Hin Lee; Kumar Sudesh (Malaysian Journal of Microbiology, 2012)
Aims: Polyhydroxyalkanoates (PHA) having various molar fractions of 4-hydroxybutyrate has been successfully synthesized by Delftia acidovorans.Methodology and results: The monomer compositions of the PHA were varied by cultivating the bacterium in a mixture of 1,4-butanediol and sodium valerate, γ-butyrolactone and sodium valerate as well as 4-hydroxybutyric acid and sodium valerate, which resulted in the production of PHA terpolymers. Although the highest terpolymer content achieved was only 57 wt% of the dry cell weight, the 4HB molar fractions can be regulated from 2-50 mol% when culture conditions such as initial pH, inoculum concentration and aeration were varied. The in vitro degradation of [P(3HB-co-50 % 4HB)] synthesized by D. acidovorans were also studied by monitoring the erosion rate of the copolymer in aqueous solutions of lipases (Lipase A ‘Amano’ 12 and Newlase F). Results have shown that the types of lipases, concentration of lipase solution and pH of the buffer solution influenced the degradation rate of the PHA copolymer.Conclusion, significance and impact of the study: The overall results have shown that D. acidovorans is a very promising strain for the production of 4HB containing PHAs with specific compositions which are very suitable to be tailor made into biodegradable and biocompatible materials for medical applications.